2015
DOI: 10.5603/fm.a2018.0054
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characterization of the coronary arteries in African sheep (Ovis orientalis). Differential analysis with those of humans and other animal species

Abstract: Due to the similitude in the features of the coronary arteries between African sheep and humans, this animal model can be proposed for procedural and hemodynamic activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 20 publications
3
8
1
Order By: Relevance
“…In literature (Vincenti et al, 2014) it is believed that owing to its anatomical features are similar to human heart, the sheep heart can set a model for the studies conducted in human medicine. Besides the importance of using sheep heart as an experimental model, there were macroanatomic and morphometric studies on coronary arteries and myocardial bridges of various sheep breeds (Teke et al, 2017;Aksoy et al, 2018;Gomez et al, 2018). However, no studies on coronary arteries and myocardial bridges were found in Tuj and Hemshin sheep.…”
Section: Introductionmentioning
confidence: 99%
“…In literature (Vincenti et al, 2014) it is believed that owing to its anatomical features are similar to human heart, the sheep heart can set a model for the studies conducted in human medicine. Besides the importance of using sheep heart as an experimental model, there were macroanatomic and morphometric studies on coronary arteries and myocardial bridges of various sheep breeds (Teke et al, 2017;Aksoy et al, 2018;Gomez et al, 2018). However, no studies on coronary arteries and myocardial bridges were found in Tuj and Hemshin sheep.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, their usage as animal models to mimic the human coronary system merits careful scrutiny before findings can be extrapolated. 38,39…”
Section: Ijmsmentioning
confidence: 99%
“…Given that bovine species exhibit the most coronary artery anomalies, their usage as an animal model in better understanding the various treatment IJMS options for Type-A ADs is hence not justified, given that these findings would not necessarily accurately represent what we might see within humans. 38,39 Between porcine and ovine species however, the coronary vasculature is similar to that of humans. However, as aforementioned, much more research has been performed on the coronary arterial supply of pigs, with little to no comparative research being performed on their ovine counterparts, and as such, the former takes current precedence when selecting an animal model for Type-A AD research.…”
Section: Suitability For Use As Animal Clinical Models In Type-a Aort...mentioning
confidence: 99%
“…( James, 1965 ; Kalpana, 2003 ; Ballesteros et al, 2011 ). In addition, there is a reference to the study of the coronary tree in other types of ruminants such as the European bison ( Kupczyńska et al , 2015 ; Barszcz et al , 2020 ), sheep ( Bertho and Gagnon, 1964 ; Besoluk and Tipirdamaz, 2001 ; Aksoy et al , 2009 ; Gómez et al , 2019 ) and goats ( Lipovetsky et al , 1983 ).…”
Section: Introductionmentioning
confidence: 99%